The Effect of Feed Supplementation with Fermented Red Seaweed (Kappaphycus alvarezii) on Growth and Survival of White Shrimp (Litopenaeus vannamei) Post-Larvae Culture - Gede Suantika; Magdalena Lenny Situmorang; Felicia Irene Saputra; Ulya Alviredieta; Pingkan Aditiawati; Sastia Prama Putri (Bogor Agricultural University, Indonesia, 2021)
This study was aimed to investigate the effect of novel shrimp diet supplemention with fermented red seaweed Kappaphycus alvarezii on growth and survival of whiteleg shrimp (Litopenaeus vannamei) post-larvae culture. The research consisted of three consecutive steps: (1) preliminary study on Kappaphycus alvarezii fermentation, (2) feed formulation and proximate analysis, (3) performance test of commercial feed (C), commercial + 0.5% K. alvarezii (EF1), and commercial + 1.5% fermented K. alvarezii (EF2). Following 15 days of feeding, the highest biomass, specific growth rate and survival were achieved in EF2 treatment (1.60±0.21 g, 10.88±0.86%/d, 91.67±1.53%), significantly different from control (0.99±0.09 g, 7.72±0.63%/d, 47.00±5.00%) (p<0.05). Overall, this study suggested that the dietary supplementation of 1.5% fermented K. alvarezii can enhance the growth and survival of whiteleg shrimp during the nursery phase.